DEMOKRATISASI OTONOMI DAERAH SEBAGAI WUJUD REFORMASI BUDAYA - Mat Jalil (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2012)
Abstract The essential of Pancasila Democracy teaches the openness. The openness is a condition to make democracy has function, citizen politic participation would not exist without the openness. Regional autonomy is regional authority to arrange, and manage the interest of local people according to its initiative. Regional autonomy gives a wide chance to the people to be participated in their regional management in order to create collective prosperity. Tha active participation of people to the democratic economy development process by means of togetherness which is has mutual benefit as the participation process from, by, and to the people. Autonomy covered the competence to discuss, consider, choose, and do different act inside the private or public to achieve democracy or public beneficience. The connection between the regional as a fair framework, and the people as the agents who can determine. The connection between village as a independent law institution or based structure of law, the institutions, and the idea about democracy as a autonomous determiner. The characteristic of democracy connection and regional autonomy are political thoughts, where focusing region as a powerful position in the society. Keywords: democracy, autonomy, openness, transperancy.